Dehydrogenation Mechanism of Three Stereoisomers of Butane-2,3-Diol in Pseudomonas putida KT2440 - Liu, Yidong; Wang, Xiuqing; Ma, Liting; Lü, Min; Zhang, Wen; Lü, Chuanjuan; Gao, Chao; Xu, Ping; Ma, Cuiqing (Frontiers in Bioengineering and Biotechnology, 2021)
Pseudomonas putida KT2440 is a promising chassis of industrial biotechnology due to its metabolic versatility. Butane-2,3-diol (2,3-BDO) is a precursor of numerous value-added chemicals. It is also a microbial metabolite which widely exists in various habiting environments of P. putida KT2440. It was reported that P. putida KT2440 is able to use 2,3-BDO as a sole carbon source for growth. There are three stereoisomeric forms of 2,3-BDO: (2R,3R)-2,3-BDO, meso-2,3-BDO and (2S,3S)-2,3-BDO. However, whether P. putida KT2440 can utilize three stereoisomeric forms of 2,3-BDO has not been elucidated. Here, we revealed the genomic and enzymic basis of P. putida KT2440 for dehydrogenation of different stereoisomers of 2,3-BDO into acetoin, which will be channeled to central mechanism via acetoin dehydrogenase enzyme system. (2R,3R)-2,3-BDO dehydrogenase (PP0552) was detailedly characterized and identified to participate in (2R,3R)-2,3-BDO and meso-2,3-BDO dehydrogenation. Two quinoprotein alcohol dehydrogenases, PedE (PP2674) and PedH (PP2679), were confirmed to be responsible for (2S,3S)-2,3-BDO dehydrogenation. The function redundancy and inverse regulation of PedH and PedE by lanthanide availability provides a mechanism for the adaption of P. putida KT2440 to variable environmental conditions. Elucidation of the mechanism of 2,3-BDO catabolism in P. putida KT2440 would provide new insights for bioproduction of 2,3-BDO-derived chemicals based on this robust chassis.